2016
DOI: 10.1016/j.heliyon.2016.e00071
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a flash flood on drinking water quality: case study of areas most affected by the 2012 Beijing flood

Abstract: In this study, we present a method for identifying sources of water pollution and their relative contributions in pollution disasters. The method uses a combination of principal component analysis and factor analysis. We carried out a case study in three rural villages close to Beijing after torrential rain on July 21, 2012. Nine water samples were analyzed for eight parameters, namely turbidity, total hardness, total dissolved solids, sulfates, chlorides, nitrates, total bacterial count, and total coliform gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…The factor score of each VF multiplied by its variance contribution rate extracts a common factor, which can then be weighted to obtain composite scores for each sampling site. For any sampling site, the larger the factor score, the more serious the pollution at that point [31]. It is seen from the scores that the pollution levels at the sampling points varied (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The factor score of each VF multiplied by its variance contribution rate extracts a common factor, which can then be weighted to obtain composite scores for each sampling site. For any sampling site, the larger the factor score, the more serious the pollution at that point [31]. It is seen from the scores that the pollution levels at the sampling points varied (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…During the 2012 Beijing flooding, Sun et al [34] found the impact of flash flooding in drinking water quality. Nine water samples were collected and analyzed for eight parameters, namely turbidity, total hardness, total dissolved solids, sulfates, chlorides, nitrates, total bacterial count, and total coliform groups.…”
Section: Discussionmentioning
confidence: 99%
“…Due to human influence, the expert opinion method can be subjective and uncertain. In an attempt to reduce the subjectivity in parameter selection, statistical tools have been developed and widely adopted as common practice [15,20,[34][35][36]. Hypothetically, this might be the most objective method, but still, the human influence is evident on the choice of data that is statistically analyzed, hence compromising the accuracy of the procedure [5].…”
Section: Selection Of Water Quality Parametersmentioning
confidence: 99%
“…Hypothetically, this might be the most objective method, but still, the human influence is evident on the choice of data that is statistically analyzed, hence compromising the accuracy of the procedure [5]. Nevertheless, through the use of pattern recognition; statistical methods remain the most powerful technique for interpreting the variance between a large number of variables and convert them into smaller groups of independent variables [34,36].…”
Section: Selection Of Water Quality Parametersmentioning
confidence: 99%